Behavioral Treatment of Chronic Insomnia in Older Adults: Does Nocturia Matter?. Issue 4 (1st April 2014) - Tyagi, Shachi; Resnick, Neil M.; Perera, Subashan; Monk, Timothy H.; Hall, Martica H.; Buysse, Daniel J.
Abstract: Objective: To evaluate the impact of nocturia on the therapeutic response of chronic insomnia to behavioral treatment in older adults. Methods: Secondary analysis of a randomized clinical trial designed to assess the efficacy of brief behavioral treatment of insomnia (BBTI) vs. an information-only control (IC) in 79 community-dwelling older adults with chronic insomnia. For the current analysis, participants were stratified into 2 groups: those with self-reported nocturia at baseline i.e., ≥ 1 void/night (N = 30; 16 IC, 14 BBTI) and those without nocturia (N = 49; 24 IC, 25 BBTI). We then determined the impact of BBTI on sleep, sleep quality, and nocturia as assessed by self-report, actigraphy, and polysomnography Results: Individuals without baseline nocturia responded well to BBTI with significant decrease in sleep latency, wake after sleep onset, and total sleep time assessed by sleep diary and actigraphy; these changes were significantly greater than those in the IC group. In comparison, changes in the same sleep parameters among participants with nocturia were not significantly different from the IC control. Although BBTI showed significant improvement in sleep quality in groups with and without nocturia (as assessed by PSQI and sleep diary), the effect size of these improvements was larger in those without nocturia than in those with nocturia (PSQI d = 0.82 vs. 0.53, diary sleep quality d = 0.83 vs. 0.51). Conclusions: These secondary analyses suggest that brief behavioral treatment of insomnia may be more efficacious in improving insomnia in participants without nocturia. Addressing nocturia may improve the efficacy of behavioral insomnia treatment.